Werkstoffkundliche Untersuchungsergebnisse einer im 17. Jahrhundert aus Gusseisen gefertigten englischen Schiffskanone = Results of metallurgical analysis of a 17th century English cast iron naval gun - Preßlinger, Hubert; Pichler, Bernhard; MacLeod, Ian D. (Berg- und hüttenmännische Monatshefte, 2012)
Summary: The 16th and 17th century saw an increase in cast iron production, as European sea powers began to equip both their battleships and merchant vessels with cast iron guns. In the 17th century the English had a clear technological advantage over other European nations due, thanks to their large number of iron ore and hard coal deposits, and to early experience in the mass production of guns. A sample was taken from an English 17th century gun of a ship and submitted to metallurgical examination. The gun, manufactured in the early 17th century, consisteds of pearlitic cast iron (grey cast iron) with primary lamellar graphite. Other structural components included tertiary solidified steatite (ternary phosphide eutectic) as well as the (Mn,Fe) S compounds developing at the end of the process. The chemical analysis of the gun - using microanalytical methods - showed 6.56 % carbon, 1.25 % manganese, 0.76 % silicon, 0.63 % phosphorus, and 0.22 % sulphur (all percentages by mass). The high carbon content is proof that the cast iron was melted in a blast furnace (first-melt casting). The high sulphur content is indicative of the furnace being charged with mineral coal as an energy carrier.
Gesehen am 01.04.2020